Microbiologic epidemiology depending on time to occurrence of prosthetic joint infection: a prospective cohort study. (March 2019) - Triffault-Fillit, C.; Ferry, T.; Laurent, F.; Pradat, P.; Dupieux, C.; Conrad, A.; Becker, A.; Lustig, S.; Fessy, M.H.; Chidiac, C.; Valour, F.; ,
Abstract: Objectives: The high microbiologic diversity encountered in prosthetic joint infection (PJI) makes the choice of empirical antimicrobial therapies challenging, especially in cases of implant retention or one-stage exchange. Despite the risk of dysbiosis and toxicity, the combination of vancomycin with a broad-spectrum β-lactam is currently recommended in all cases, even if Gram-negative bacilli (GNB) might be less represented in late PJI. In this context, this study aimed to describe the microbiologic epidemiology of PJI according to the chronology of infection. Methods: This prospective cohort study (2011–2016) evaluated the microbiologic aetiology of 567 PJI according to time of occurrence from prosthesis implantation—early (<3 months), delayed (3–12 months) and late (>12 months)—as well as mechanism of acquisition. Results: Initial microbiologic documentation ( n  = 511; 90.1%) disclosed 164 (28.9%) Staphylococcus aureus (including 26 (16.1%) methicillin-resistant S. aureus ), 162 (28.6%) coagulase-negative staphylococci (including 81 (59.1%) methicillin-resistant coagulase-negative staphylococci), 80 (14.1%) Enterobacteriaceae, 74 (13.1%) streptococci and 60 (10.6%) Cutibacterium acnes. Considering nonhaematogenous late PJI ( n  = 182), Enterobacteriaceae ( n  = 7; 3.8%) were less represented than in the first year after implantation ( n  = 56; 17.2%; p <0.001), without difference regarding nonfermenting GNB (4.6% and 2.7%, respectively). The prevalence of anaerobes ( n  = 40; 21.9%; including 32 (80.0%) C. acnes ) was higher in late PJI (p <0.001). Consequently, a broad-spectrum β-lactam might be useful in 12 patients (6.6%) with late PJI only compared to 66 patients (20.3%) with early/delayed PJI (p <0.001). Conclusions: Considering the minority amount of GNB in late postoperative PJI, the empirical use of a broad-spectrum β-lactam should be reconsidered, especially when a two-stage exchange is planned.